The effect of learning with direct playing style on the accuracy of table tennis serve in 8-10-year-old players - Ali Jalal Obaid; Loaiy Hussein; Raid Mhawes Zighair (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.